2013
DOI: 10.1007/s12035-013-8608-2
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Epigallocatechin-3-Gallate Ameliorates Learning and Memory Deficits by Adjusting the Balance of TrkA/p75NTR Signaling in APP/PS1 Transgenic Mice

Abstract: Alzheimer's disease (AD) is pathologically characterized by deposition of β-amyloid (Aβ) peptides, which closely correlates with the balance of nerve growth factor (NGF)-related TrkA/p75NTR signaling. (−)-Epigallocatechin-3-gallate (EGCG) is used for prevention and treatment of many neurodegenerative diseases, including AD. However, whether the neuroprotective effects of EGCG treatment were via modulating the balance of TrkA/p75NTR signaling was still unknown. In this study, we found that EGCG treatment (2 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 48 publications
5
67
1
Order By: Relevance
“…The findings of this study were consistent with our previous studies 6, 32 and other investigations that examined the neuroprotective properties of EGCG on peripheral neuropathies, 33 degenerative diseases, such as Alzehiemer's disease and Parkinson's disease, and traumatic brain injury. [34][35][36] Parallel to other studies, our study demonstrates that administering EGCG (50 mg/kg) to sciatic nerve-injured rats improved neurological recovery in these rats and increased the survival of neurons in both the dorsal and ventral horns of spinal cords of EGCG-treated rats on histological examination. Neurological recovery was measured as a function of the EPT, allodynia latency, paw pressure latency, hot-plate latency, and tail flick.…”
Section: Discussionsupporting
confidence: 83%
“…The findings of this study were consistent with our previous studies 6, 32 and other investigations that examined the neuroprotective properties of EGCG on peripheral neuropathies, 33 degenerative diseases, such as Alzehiemer's disease and Parkinson's disease, and traumatic brain injury. [34][35][36] Parallel to other studies, our study demonstrates that administering EGCG (50 mg/kg) to sciatic nerve-injured rats improved neurological recovery in these rats and increased the survival of neurons in both the dorsal and ventral horns of spinal cords of EGCG-treated rats on histological examination. Neurological recovery was measured as a function of the EPT, allodynia latency, paw pressure latency, hot-plate latency, and tail flick.…”
Section: Discussionsupporting
confidence: 83%
“…Most of the studies have measured spatial learning and memory using the Morris water maze or 8-arm maze [18-20]. Some studies also included the Y-maze and passive avoidance tests [17,63]. The passive avoidance test is similar to the contextual fear conditioning task in the sense that both tasks measure associative memory of a context previously paired with an aversive foot shock.…”
Section: Discussionmentioning
confidence: 99%
“…They found a benefit in diabetic mice that displayed impaired baseline performance, but no effect was found in the normal control mice, consistent with our results. In fact, most of the studies that found a positive influence of EGCG on cognitive performance found the effect in an animal that was impaired to begin with [17-19,63]. Few studies found benefits in normal mice but see [20].…”
Section: Discussionmentioning
confidence: 99%
“…EGCG has shown to exert such activity by influencing cellular signal transduction pathways and reactive oxygen species [38,39]. Previous studies have shown that gallate esters are important for the association of polyphenols with proteins, probably because they mediate weak hydrophobic interactions with proline-rich regions in target proteins, which is a prerequisite for subsequent hydrogen bond formation [40].…”
Section: Implication Of Therapeutic Strategy For Neurodegenerative DImentioning
confidence: 99%